LPC: A Good Source of Cyanocobalamine (B12), Ascorbic Acid (Vitamin C) and Folic Acid (Vitamin B9) - Sayyed Iliyas2, K.V.Badar1* and (Journal of Experimental Sciences, 2010)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> LPC of twenty plants was prepared. Cyanocobalamine (B12), ascorbic acid (vitamin C) and folic acid (vitamin B9) was estimated from LPC. Higher yield of vitamin B12 (cynocobalamine) in wet LPC was recorded in Bennicasa hispida, Coccina grandis and Vigna mungo. The maximum yield of vitamin C (Ascorbic acid) and folic acid was recorded in Vigna mungo. Â  --------------------------------------------------------------------- 1Department of Botany, Yeshwantrao Chavan College, Sillod, Dist- Aurangabad (M.S.), India; 2Department of Botany, AKIâ€™S Poona College of arts, Science and commerce, Pune camp, Pune (M.S.), India * Corresponding Author, Email: badarkakasaheb@yahoo.in Please Cite This Article As: K.V.Badar and Sayyed Iliyas. 2010. LPC: A Good Source of Cyanocobalamine (B12), Ascorbic Acid (Vitamin C) and Folic Acid (Vitamin B9). J. Exp. Sci. 1(2): 15-17.